(untitled) (Environment & Health, 2024)
Purpose: to evaluate the peculiarities of changes in the health of overweight people and to resolve a number of issues related to improving diagnostics and stratification of the degree of risk of developing arterial hypertension in them during an in-depth medical examination. Materials and methods. 30 adult patients, aged from 24 to 86 years оld, were examined, of which 15 were women and 15 were men. Among the anthropometric studies, the following were determined: height; weight; body mass index, which was calculated according to the formula (ratio of weight (kg) to height (square meters)); blood pressure (systolic and diastolic) was determined using a tonometer; due to laboratory studies, the following was determined: creatinine (colorimetric determination method), cystatin-c and glomerular filtration rate (calculated method of determination) (all laboratory parameters were determined on an empty stomach and in the morning; the last food intake was 8 hours before blood sampling, water balance was allowed to be maintained before blood sampling). Statistical data processing was carried out using a software package, the relationship between quantitative indicators using Pearson’s correlation analysis (rs ). Statistical probability was assessed using the Student’s parametric t-test. The difference was considered probable with p